Effect of peer support nursing on improvement of caregiver preparedness for care of low anal fistula in infants (同伴支持式护理提升婴儿低位肛瘘照顾者准备度的研究) - GUO Yufan (郭雨凡); WANG Yanmei (王晏美); LI Jianan (李佳楠); LAI Lixia (来丽霞); WANG Yanzhi (王艳芝) (中西医结合护理)
Objective To investigate the effect of peer support nursing on caregiver preparedness for care of low anal fistula in infants. Methods A prospective, randomized, single-blind control study was conducted, and 60 cases of infants with anal fistula were included and randomly divided into two groups. Totally 60 primary caregivers of infants were also included as research subjects. Caregivers of infants in both control group and observation group received routine health education before discharge from hospital, and those in the observation group were given peer support nursing. The caregiver preparedness and anxiety status were evaluated and compared between two groups. Results The total score of Caregiver Preparedness Scale (CPS) in the observation group was higher than that in the control group (P＜0. 01). The score of short-form Anxiety Assessment Scale in the observation group was (2. 53±1. 07), which was lower than (5. 00±1. 08)in the control group (P＜0. 01). Conclusion Peer support nursing is potentially effective to improve caregivers preparedness and reduces their degree of anxiety. It has positive significance for promoting postoperative rehabilitation of infant patients with anal fistula. (目的 探讨运用同伴支持式护理干预提升婴儿低位肛瘘照顾者准备度的效果。方法 采用前瞻性、随机、单盲对照研究方法, 纳入60例婴儿低位肛瘘患儿, 术前进行肛肠专科检查及肛管直肠超声检查, 根据随机数字法分为两组。对照组采用常规出院指导, 观察组在对照组基础上采用同伴支持式护理。每位患儿选取1位照顾者参与研究, 共调查60位患儿照顾者。评价2组患儿照顾者准备度和焦虑指标。结果 观察组患儿照顾者的照顾者准备度量表(CPS)总分高于对照组患儿照顾者, 差异有统计学意义(P＜0. 01)。简易焦虑问卷评价结果显示, 观察组评分(2. 53±1. 07)分, 低于对照组的(5. 00±1. 08)分, 差异有统计学意义(P＜0. 01)。结论 同伴式支持护理干预能够提高照顾者的准备能力, 减轻焦虑程度, 对促进婴儿低位肛瘘患儿康复具有积极意义。)